2013
DOI: 10.5694/mja12.11334
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a genomic assay (Oncotype DX) on adjuvant treatment recommendations in early breast cancer

Abstract: The Oncotype DX recurrence score has a major impact on adjuvant treatment decision making in the MDM setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 18 publications
6
38
1
Order By: Relevance
“…Studies with a similar design have been reported from other countries [16][17][18][19][20][21][22]. They showed that the initial treatment recommendation is heterogeneous with the initial proportion of patients recommended chemotherapy ranging from 30% to 59%.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Studies with a similar design have been reported from other countries [16][17][18][19][20][21][22]. They showed that the initial treatment recommendation is heterogeneous with the initial proportion of patients recommended chemotherapy ranging from 30% to 59%.…”
Section: Discussionmentioning
confidence: 64%
“…The Recurrence Score has also been validated as a predictive marker for the magnitude of adjuvant chemotherapy benefit [2,11] with a significant benefit in patients with high Recurrence Score values (28% absolute benefit in 10-year risk of distant recurrence) and minimal, if any, benefit from chemotherapy in patients with low values. In patients with intermediate values (Recurrence Scores of [18][19][20][21][22][23][24][25][26][27][28][29][30], the available data cannot rule out that some patients may benefit from chemotherapy [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although many smaller studies have shown that the RS assay influences clinicians' recommendation for chemotherapy, [15][16][17][18] the first nationwide study that involved Medicare beneficiaries recently showed no change in the use of chemotherapy after adoption of the RS assay. 19 The NCCN Clinical Practice Guidelines in Oncology for Breast Cancer contain a footnote suggesting that the RS assay can be considered in select patients with 1 to 3 involved ipsilateral axillary lymph nodes, with ER-positive, HER2-negative EBC to guide the addition of combination chemotherapy to standard hormone therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that use of the Oncotype DX Breast Cancer Assay affects treatment recommendations [14][15][16][17][18][19][20][21][22][23][24][25][26]. These studies demonstrated that analysis of treatment decisions before and after receipt of Recurrence Score information showed approximately a 30% decrease in chemotherapy recommendations [27].…”
Section: Introductionmentioning
confidence: 99%